Effects Of Simvastatin On Histomorphological And Biochemical Parameters Of The Thyroid In Rats - Qamar, Abdullah; Khan, Hammad Gul; Yaqub, Raja Khalid; Abdullah, Muhammad Saad; Ahmed, Naeema; Asad , Ayesha (Journal of Rawalpindi Medical College, 2025)
Objective: This study intended to explore the effect of simvastatin on the thyroid gland’s biochemical function and histological structure in a rat specimen. Methodology: An experimental study using a controlled laboratory model from January 2022 to January 2023. This study was conducted at Army Medical College, Armed Forces Institute of Pathology Rawalpindi in collaboration with the National Institute of Health Islamabad, Rawalpindi over one year. Forty male Sprague-Dawley rats weighing approximately 250 grams and between the ages of 3-4 weeks were randomly assigned into identical groups: a control group (A) and an experimental group (B), which received simvastatin for 12 weeks. After the test, rats were euthanized, and their thyroid glands were harvested for analysis. The glands were examined histologically to assess for structural changes, inclusive of size of diameter of thyroid follicles. In addition, serum levels of thyroxine (T4) and thyroid-stimulating hormone (TSH) were assayed. Data have been analyzed using SPSS software version 23. Statistical significance was expressed using Chi-square checks for qualitative records and independent sample t-test for quantitative comparisons, with P < 0.05 considered significant. Results: Simvastatin treatment resulted in noteworthy differences in the biochemical profile, with a noticeable decrease in serum T3 level (p=0.001) s and a rise in thyroid-stimulating hormone (TSH) (p=0.001) levels compared to the control group. Supplementary noticeable histological changes in the thyroid glands of the rats were detected and characterized by decreased diameter of thyroid follicles (p=0.001). Conclusions: The results of this study specify that Simvastatin induces considerable alterations in endocrine profile and variations in thyroid gland histology in rats. These results propose that the drug could influence thyroid health, with probable implications for long-term statin use in clinical situations. Keywords: Hypothyroidism, Hyperthyroidism, Thyroid Diseases, Apoptosis, Endocrine Gland, Metabolism